IMPROVING THE BEGINNING READING ABILITY OF 5-6 YEAR OLD CHILDREN THROUGH LEGO LETTER MEDIA - Atikah Azzahra, Eneng Sri Susilawati, Suci Aprilyati Ruiyat (JURNAL PENDIDIKAN DAN PENELITIAN SERUMPUN MENGAJAR, 2024)
This study was motivated by the low ability of 5-6 year old children to read beginning at PAUD Daar El Hasanah, Jawilan District. This study aims to determine the use of lego letter media on the ability of beginning reading in children aged 5-6 years at PAUD Daar El Hasanah, Jawilan District in the 2023-2024 academic year, conducted from February to June 2024. The subjects of this study were children aged 5-6 years in group B with a total of 14 people consisting of 7 boys and 7 girls. This research method uses Classroom Action Research (PTK) which refers to Kemmis and McTaggar who use four components of action research, namely planning, action, observation, and reflection. Based on the developmental data, the ability of children's beginning reading in Group B at PAUD Daar El Hasanah totaling 14 people, at the time of pre-research the average ability of children was 30.8%, after being given action in cycle I there was an increase with an average of 68.7%, this shows that there is an increase in children's ability on average by 37.9%. Based on these data, this research is said to have not met the success criteria, so the researchers took action in cycle II. The results of silkus II data obtained data on the improvement of early reading skills in children aged 5-6 years increased by an average of 89.7%, so there was an increase from cycle I to silkus II by 21%.